2020
DOI: 10.1111/jcmm.15280
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR4435‐2HG potentiates the proliferation and invasion of glioblastoma cells via modulating miR‐1224‐5p/TGFBR2 axis

Abstract: Glioblastoma (GBM) belongs to the high‐grade (IV) gliomas with extremely poor prognosis. Accumulating evidence uncovered the key roles of long non‐coding RNAs (lncRNAs) in GBM development. This study aimed to determine the biological actions and the clinical relevance of lncRNA MIR4435‐2 Host Gene (MIR4435‐2HG) in GBM. Data from GEPIA database showed that MIR4435‐2HG was up‐regulated in GBM tissues and high expression of MIR4435‐2HG correlated with shorter overall survival of GBM patients. Further experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…LncRNAs have been verified to play a pivotal role in human disease including GBM by an increasing number of studies. For example, LncRNA MIR4435-2HG potentiates the proliferation and invasion of glioblastoma cells via modulating miR-1224–5p/TGFBR2 axis ( Xu et al, 2020 ). LncRNA MATN1-AS1 prevents glioblastoma cell from proliferation and invasion via RELA regulation and MAPK signaling pathway ( Han et al, 2019 ), suggesting that LncRNAs could be used as diagnostic biomarkers and potential therapeutic targets in GBM in the future.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been verified to play a pivotal role in human disease including GBM by an increasing number of studies. For example, LncRNA MIR4435-2HG potentiates the proliferation and invasion of glioblastoma cells via modulating miR-1224–5p/TGFBR2 axis ( Xu et al, 2020 ). LncRNA MATN1-AS1 prevents glioblastoma cell from proliferation and invasion via RELA regulation and MAPK signaling pathway ( Han et al, 2019 ), suggesting that LncRNAs could be used as diagnostic biomarkers and potential therapeutic targets in GBM in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is a fast‐growing type of aggressive and lethal primary brain tumour 1,2 . Because the pathologic mechanisms of GBM are not fully understood, more research is needed to identify effective predictive biomarkers and therapeutic targets for GBM 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…MIR4435-2HG has also been observed to play a role in several cancers through this regulatory mechanism. For example, MIR4435-2HG knockdown suppressed ovarian cancer cell proliferation, invasion, and migration through the miR-128-3p/CDK14 axis (11), MIR4435-2HG promoted the proliferation and invasion of glioblastoma cells by regulating the miR-1224-5p/TGFBR2 axis (12), and MIR4435-2HG acted as a ceRNA to upregulate YAP1 expression by sponging miR-206 and promoted colorectal cancer growth and metastasis (13). To investigate the mechanism of MIR4435-2HG regulation in HNSCC, bioinformatics analysis indicated that miR-383-5p, a tumor suppressor in several types of cancers, including triple-negative breast cancer, ovarian cancer, and gastric cancer (31-33), has potential MIR4435-2HG binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MIR4435-2HG knockdown was shown to suppress the proliferation and invasion of ovarian cancer cells (11). MIR4435-2HG expression is upregulated in glioblastoma tissues and is associated with shorter overall survival in patients with glioblastoma (12). In addition, it serves as an oncogene in colorectal cancer, oral squamous cell carcinoma, non-small cell lung cancer, and gastric cancer (10,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%